Pelaksanaan Pembelajaran Daring di masa COVID-19 di SMP Negeri 3 Marioriwawo - Alvina Nurulita; Abdul Hakim; Nurhikmah H (Universitas Negeri Makassar, 2021)
This study aims to describe 1) How is the process of implementing online learning 2) the advantages and disadvantages of online learning during the implementation of online learning 3) Obstacles to the implementation of online learning during the COVID-19 period in Indonesian language subjects. The data analysis technique used was descriptive-analytical technique. The results of the study indicate that the implementation of online learning is a process of implementing learning that students are required to study alone in their respective homes. The disadvantages and advantages of online learning are that it is easy because teachers can give assignments and students send assignments more easily because they are sent via WhatsApp, the drawback is the lack of student activity in participating in teaching and learning activities. The obstacle is the ineffectiveness of learning due to lack of supervision from parents and students experiencing boredom during the online learning process.